Distribution and monitoring of power and mechanisms to increase the efficiency of power in Shiite political thought - Abbaszadeh, Hassan (2021)
The results of this study, due to the many ambiguities in the field of power in Islam, can be considered by government organizations such as the Guardian Council and researchers in the fields of jurisprudence and law, natural and legal persons who somehow deal with sources of power, and students and professors of political science. And rights to be placed. Depending on the subject of the research, the method of collecting materials in an analytical and descriptive manner and by studying valid sources in the library and, if possible, the interview method will be on the agenda so that first the desired sources are studied and after analysis, In the end, this research aims to achieve results and make suggestions for improving the current situation; Therefore, first the required resources from various sources of presence in the library, digital libraries, existing software such as comprehensive Ahl al-Bayt and Shiite history and existing articles, treatises and dissertations, selected and after studying and separating the required materials, receipts Necessary from the required resources and then as a complete research, its compilation will be completed. The present study will have a new approach to all aspects of power in Shiite political thought and the author will try to have a comprehensive look at the jurisprudential principles of this issue based on Quranic arguments, narration, sayings of jurists and rational arguments.